Concordant Changes in Gene Expression and Nucleotides Underlie Independent Adaptation to Hydrogen-Sulfide-Rich Environments. (12th September 2018) - Brown, Anthony P; Arias-Rodriguez, Lenin; Yee, Muh-Ching; Tobler, Michael; Kelley, Joanna L
Abstract: The colonization of novel environments often involves changes in gene expression, protein coding sequence, or both. Studies of how populations adapt to novel conditions, however, often focus on only one of these two processes, potentially missing out on the relative importance of different parts of the evolutionary process. In this study, our objectives were 1) to better understand the qualitative concordance between conclusions drawn from analyses of differential expression and changes in genic sequence and 2) to quantitatively test whether differentially expressed genes were enriched for sites putatively under positive selection within gene regions. To achieve this, we compared populations of fish (Poecilia mexicana ) that have independently adapted to hydrogen-sulfide-rich environments in southern Mexico to adjacent populations residing in nonsulfidic waters. Specifically, we used RNA-sequencing data to compare both gene expression and DNA sequence differences between populations. Analyzing these two different data types led to similar conclusions about which biochemical pathways (sulfide detoxification and cellular respiration) were involved in adaptation to sulfidic environments. Additionally, we found a greater overlap between genes putatively under selection and differentially expressed genes than expected by chance. We conclude that considering both differential expression and changes in DNA sequence led to a more comprehensive understanding of how these populations adapted to extreme environmental conditions. Our results imply that changes in both gene expression and DNA sequence—sometimes at the same loci—may be involved in adaptation.